PENGARUH TRANSFER PELATIHAN DAN KUALITAS KEHIDUPAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING (Studi Pada Perusahaan Ayooklik) - Shafira Elza; Ismi Darmastuti (Jurnal Akuntansi dan Pajak, 2023)
The purpose of this study is to analyze and explain the effect of training transfer and quality of work life on employee performance with organizational commitment as an intervening variable (studies on Ayooklik.com employees). The population of this study were all permanent employees of Ayooklik.com, the sampling technique used was a non-probability sampling technique with a purposive sampling technique. Data collection used a questionnaire with the criteria of respondents who had attended training held by the company in the period January - December 2021. There were 61 questionnaires of data taken. Processing and data analysis using SEM (Structural Equation Modeling) with PLS (Partial Least Square) 3.0 technique. The results of this study found that the transfer of training had a significant positive effect on employee performance; quality of work life has a significant positive effect on employee performance; transfer of training has a significant positive effect on organizational commitment; the quality of work life has a significant positive effect on organizational commitment; and organizational commitment has a significant positive effect on employee performance. Findings are discussed based on previous evidence, and implications for companies. Keywords: Training Transfer, Quality of Work Life, Organizational Commitment, Employee Performance.